Date palm fruit (var. Ajwa) promotes proliferation of human bone marrow mesenchymal stem cells: potential natural booster for endogenous stem cells growth - M.L. Masniza; R. Nur Syahrina; A.R. Hayati; A.A. Asral Wirda; M.M. Nur Fariha; Zetty Nadia Mohd Zain; Fadlul Azim Fauzi Mansur (International Society for Horticultural Science (ISHS), 2024)
Indexed by WOS/Scopus/ERA